1996
DOI: 10.2165/00002018-199615010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drug-Induced Hepatic Disorders

Abstract: The nonsteroidal anti-inflammatory drugs (NSAIDs) are the most frequently used medications worldwide for the treatment of a variety of common chronic and acute inflammatory conditions. The association between NSAIDs and liver disease is poorly documented, the exceptions being sulindac and, to a lesser degree, diclofenac. The incidence of liver disease is very low and is relatively unimportant compared with the risk of peptic ulcer disease and gastrointestinal bleeding. Reports of hepatic injury range from insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…The lesions seen in histological studies are similar to those related to acetaminophen and centrilobular necrosis in severe cases (33). The female gender, being aged over 50 years, and the presence of immune disorders have all been reported as important risk factors in various studies (34). Further, a cohort study found that the risk of liver injury is increased tenfold in patients with rheumatoid arthritis when compared to patients with osteoarthritis (29).…”
Section: Contextmentioning
confidence: 99%
“…The lesions seen in histological studies are similar to those related to acetaminophen and centrilobular necrosis in severe cases (33). The female gender, being aged over 50 years, and the presence of immune disorders have all been reported as important risk factors in various studies (34). Further, a cohort study found that the risk of liver injury is increased tenfold in patients with rheumatoid arthritis when compared to patients with osteoarthritis (29).…”
Section: Contextmentioning
confidence: 99%
“…The incidence of liver disease is very low and is relatively unimportant compared with the risk of peptic ulcer disease and gastrointestinal bleeding. Reports of hepatic injury range from insignificant and transient liver enzyme elevation to severe and fulminant hepatitis (Manoukian and Carson 1996). Long-term exposure to the anti-inflammatory agent such as phenylbutazone induces kidney tumors in rats and liver tumors in mice (Kari et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Other study end points, such as liver injury, acute renal failure, blood dyscrasia, skin disorders, and anaphylaxis were rare, in agreement with results of other studies. [14][15][16][17][18][19] It is reassuring that no other major adverse events were identified except three cases of liver injury.…”
Section: Discussionmentioning
confidence: 99%